Characterization of a new strain of Metarhizium novozealandicum with potential to be developed as a biopesticide. Issue 4 (2nd October 2021) - Villamizar, Laura F.; Barrera, Gloria; Hurst, Mark; Glare, Travis R.
ABSTRACT: The fungal species Metarhizium novozealandicum, that occurs only in New Zealand and Australia has been poorly studied. In this work, a new strain of M. novozealandicum isolated from a larva of Wiseana sp. is described based on morphology, genomic multilocus (ITS, EF-1α and β-tubulin) phylogeny, growth in different culture media and insecticidal activity. The isolate AgR-F177 was clustered in the same clade with M. novozealandicum . AgR-F177 colonies developed faster on Sabouraud Dextrose Agar (SDA) than on Potato Dextrose Agar (PDA) when incubated at 25°C, with no growth observed at 30°C on either media. Conidia yield on an oat-based medium in semisolid fermentation was 7.41 x 10 8 conidia/g of substrate and a higher yield of 1.68 x 10 9 conidia/g of substrate was obtained using solid fermentation on cooked rice. AgR-F177 formed microsclerotia (MS) in liquid fermentation after 7 days reaching the maximum yield of 3.3 × 10 3 MS/mL after 10 days. AgR-F177 caused mortality in Wiseana copularis, Costelytra giveni and Plutella xylostella larvae with efficacies up to 100%, 69.2%, and 45.7%, respectively. The ease of production of AgR-F177 with different fermentation systems and its pathogenicity against different insect pests reveal its potential as a new biopesticide.